2020
DOI: 10.1021/acscentsci.9b01071
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale All-Atom Influenza Virus Simulations Suggest New Substrate Binding Mechanism

Abstract: Influenza virus circulates in human, avian, and swine hosts, causing seasonal epidemic and occasional pandemic outbreaks. Influenza neuraminidase, a viral surface glycoprotein, has two sialic acid binding sites. The catalytic (primary) site, which also binds inhibitors such as oseltamivir carboxylate, is responsible for cleaving the sialic acid linkages that bind viral progeny to the host cell. In contrast, the functional annotation of the secondary site remains unclear. Here, we better characterize these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 66 publications
2
116
1
Order By: Relevance
“…Also, modelling of the respiratory droplets embedding the virus (which contain mucosal biopolymers, lipids and salts 34 ) and how these droplets interact with materials and textiles is of the highest interest. A simulation study of these factors will require the use of mesoscale models, which may be build from relevant experimental data -which is still unavailable-or eventually from the results of atomistic molecular modelling, as has been done recently for mesoscale simulations of a full influenza virus 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, modelling of the respiratory droplets embedding the virus (which contain mucosal biopolymers, lipids and salts 34 ) and how these droplets interact with materials and textiles is of the highest interest. A simulation study of these factors will require the use of mesoscale models, which may be build from relevant experimental data -which is still unavailable-or eventually from the results of atomistic molecular modelling, as has been done recently for mesoscale simulations of a full influenza virus 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Within this framework, the contribution of glycoinformatics tools and databases represents an essential resource to advance glycomics [11][12][13][14][15], while molecular simulations fit in very well as complementary and orthogonal techniques to support and advance structural glycobiology research. Indeed, current high performance computing (HPC) technology allows us to study realistic model systems [16,17] and to reach experimental timescales [18], so that computing can now contribute as one of the leading research methods in structural glycobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding OVs, the computational hardware, currently available in the majority of the computational chemistry labs, cannot sufficiently simulate so large and complex systems, nevertheless some researchers demonstrated that the simulation of an entire viral capsid is possible [170,171] suggesting that, by improving the computational power, the computational design of very complex systems, such as OVs, will be routinely accessible.…”
Section: Computational Chemistry In the Design Of Ddsmentioning
confidence: 99%